2014
DOI: 10.1002/2013ja019374
|View full text |Cite
|
Sign up to set email alerts
|

Outflow in global magnetohydrodynamics as a function of a passive inner boundary source

Abstract: Numerous studies of the terrestrial magnetosphere that use global magnetohydrodynamic codes have found that the model's inner boundary can act as a significant source of plasma, even if the radial velocity about the boundary is held at zero. Though inherent in many models, this “de facto outflow” is poorly understood. This work uses the Block Adaptive Tree Solar Wind Roe‐type Upwind Scheme MHD model to investigate the behavior of this type of outflow as a function of boundary conditions and solar wind drivers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Although the model reproduces the density trend observed by Polar, the radial position of this transition does not match precisely, and there are several reasons why this behavior is expected. First, while ionospheric outflow is driven by many processes, both kinetic and fluid [see, e.g., Welling et al , , and references therein], only a handful of outflow processes are captured in MHD without including a stand‐alone outflow model [ Welling and Liemohn , ]. This is especially true in the cusp.…”
Section: Magnetohydrodynamicsmentioning
confidence: 99%
“…Although the model reproduces the density trend observed by Polar, the radial position of this transition does not match precisely, and there are several reasons why this behavior is expected. First, while ionospheric outflow is driven by many processes, both kinetic and fluid [see, e.g., Welling et al , , and references therein], only a handful of outflow processes are captured in MHD without including a stand‐alone outflow model [ Welling and Liemohn , ]. This is especially true in the cusp.…”
Section: Magnetohydrodynamicsmentioning
confidence: 99%
“…Though noted by Siscoe et al (2001) and later more deeply explored by Walker et al (2003) and Welling and Ridley (2010), it was Winglee (1998) that first leveraged this behavior in a global multifluid code to include heavy ion outflow. It was subsequently shown that even when the mass density inner boundary conditions are constant, the resulting outflow away from the boundary is quite dynamic (Winglee 2002;Winglee et al 2008) and correlates strongly with cross polar cap potential (CPCP) and solar wind dynamic pressure (Welling and Liemohn 2014). The dynamic nature of these outflows, in spite of their static sources, implies that global fluid models are able to capture some fraction of the high latitude outflow acceleration.…”
Section: Sources and Global Modelsmentioning
confidence: 99%
“…Initially, global fluid models relied on simple inner boundary conditions (i.e., uni-form mass density) to passively include this source (e.g., Winglee 1998;Walker et al 2003;Zhang et al 2007). Though simple, this outflow specification can form time and space dependent outflows into the magnetosphere (Welling and Liemohn 2014) and dominate the central plasma sheet (Welling and Ridley 2010). Winglee (2002) found that if a heavy ion component was included in a simple, passive outflow source, the modeled cross polar cap potential was reduced significantly compared to an identical simulation that used an all-hydrogen inner boundary.…”
Section: Consequencesmentioning
confidence: 99%